Zespół pocysterski w Jemielnicy na Śląsku Opolskim w świetle badań terenowych - Andrzejewski, Aleksander; Kajzer, Leszek; Pietrzak, Janusz (Acta Universitatis Lodziensis. Folia Archaeologica, 1998)
The Cistercian monastery in Jemielnica, a branch of the monastery in Rudy (near Racibórz), was founded in the 80-ies and 90-ies of the 13th century and functioned until the beginning of the 19th century. Presently the post-Cistercian complex including the cloister itself and the remainings of the masonry claustrum serve the needs of the local Roman Catholic parish. The results of the research have confirmed that the erecting of the gothic church was initiated by building the polygnonally closed, buttressed presbiterium. In the second stage the vessels forming the gothic body were raised. In the 18th century, during the second building phase, the already existing sanctuary was extended towards the west and supplied with the turret body. Due to poor economic potential of the monastery the buildings had remained wooden until the 18th century. This year research has excluded the presence of earlier mansonry claustrum. Architectural observations indicating clear dissimilarity of the western wing suggest that since the very beginning the building had been planned as an abbey palace. The southern wing and the unsurvived eastern wing were used by the monks. In the southern wing body no evident transformations have been noticed, whereas there is evidence that the eastern wing, of which secondarily cloister has survived, was taken down in the 18th century. In the course of research the width of the eastern wing was defined (as 7,5 m) and a square northern chamber was identified as a capitulary. Similarly to other Cistercian buildings the complex under research has not shown traces of presence of occupation layers connected with medieval stages of its exploitation. It indicates that the complex was cleared. The relics occure outside the abbey ground. The researches in 1996, despite limited range of ground works, have led to crucial enrichment of our knowledge about the architectural transformations in Jemielnica complex and let objectify so far controversial opinions of the historians. They have also enabled broader evaluation of the architectural transformations observed in Rudy Abbey.